Comparison of the knowledge, attitude and practice of Iranian college students about tobacco use in comparison to their American and Chinese counterparts - Ahmad Fayaz-Bakhsh; Saeideh Babashahy; Lida Jarrahi; Sima Rafiei (International Journal of Preventive Medicine, 2011)
Objectives: The purpose of this survey was to compare the knowledge, attitude and practice of Iranian, American and Chinese college students about tobacco use. Methods: In this cross-sectional study, a questionnaire that was designed for the first time in comparative studies for the purpose of gathering information from American and Chinese college students was used. The students were selected by convenience sampling. Results: In Iran, 958 participants (456 male and 485 female) enrolled in the study. In addition, 1534 Chinese participants (39.7% female and 60.3% male) and 597 American participants (62.1% female and 37.9% male) were included in the study. Comparing the consumption of tobacco among college students of the three mentioned countries, it is shown that American women have more experiences in smoking cigarettes, cigars, pipes and chewing tobacco. Conclusions: This survey determined the tendency toward smoking among the students and their perception of this behavior and its outcome among the students from Iran, USA and China. It provided significant differences, however the culture dissimilarities in responding to such type of surveys should be taken into account.